Efficiency in public input provision in two asymmetric jurisdictions with imperfect labour markets - Holger Gillet; Johannes Pauser (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
This paper examines efficiency in public input provision in two large jurisdictions with imperfect labour markets. It analyses how equilibrium capital tax rates and public input provision levels differ between asymmetric jurisdictions that can strategically influence the interest rate on the common capital market in an international tax competition setting. In contrast to the scenario assuming competitive labour markets, the non-cooperative equilibrium is inefficient also when governments have capital and head taxes at disposal. As a source of both the distortion in the capital allocation between jurisdictions and the inefficiency in public input provision, which can be determined in at least one of the jurisdictions, we identify the governments' incentives to decrease unemployment, and a pecuniary externality [De- Pater, J., Myers, G., 1994. Strategic capital tax competition: a pecuniary externality and a corrective device. Journal of Urban Economics 36, 66-78.] in both jurisdictions. Efficiency in public input provision can be restored, however, if the set of fiscal instruments available for regional policy makers is extended by a labour tax. – – Dieses Papier befasst sich mit der effizienten Bereitstellung produktiver öffentlicher Güter in zwei großen Gebietskörperschaften, die jeweils Marktmacht auf dem gemeinsamen Kapitalmarkt haben und sich durch imperfekte Arbeitsmärkte auszeichnen. Unter diesen Rahmenbedingungen können die Gebietskörperschaften auch den internationalen Kapitalmarktzins - und damit Zahlungen für Kapitalimporte bzw. Erträge aus Kapitalexporten - durch ihre Fiskalpolitik strategisch beeinflussen. Das Papier leitet die optimalen Kapitalsteuersätze und Bereitstellungsniveaus der öffentlichen Güter in den Regionen her, die sich abhängig von den institutionellen Rahmenbedingungen auf den Arbeitsmärkten und der Richtung der Kapitalflüsse unterscheiden. Die Möglichkeit der Gebietskörperschaften durch die Wahl ihrer Steuerinstrumente die Beschäftigung sowie den Kapitalmarktzins zu beeinflussen kann dabei Ursache einer Verzerrung der Kapitalallokation und einer ineffizienten Bereitstellung öffentlicher Güter sein. Eine effiziente Bereitstellung öffentlicher Güter kann hingegen gewährleistet werden, wenn das den Gebietskörperschaften zur Verfügung stehende Steuerinstrumentarium um eine Steuer auf das Arbeitseinkommen ergänzt wird.
Keywords: H21; H71; J64; 330; Tax competition; asymmetric jurisdictions; labour market imperfections; public input provision